Generation Z's Intention to Join State-Owned Enterprises (BUMN): The Role of Employer Branding, Work-Life Balance, and Work Environment - Dwi Nuriya Aini; Frasto Biyanto; Miswanto (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study examines the influence of employer branding, work–life balance, and work environment on Generation Z's intention to join Indonesian State-Owned Enterprises (BUMN). A quantitative approach was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS. The sample consisted of 200 Generation Z respondents aged 20–28 years who had participated in at least one BUMN recruitment process. Data were collected through an online questionnaire using purposive sampling. The results indicate that employer branding (β = 0.432; p < 0.001), work–life balance (β = 0.395; p < 0.001), and work environment (β = 0.457; p < 0.001) positively and significantly influence intention to join BUMN. Among the predictors, work environment has the strongest effect. Furthermore, the three variables simultaneously explain 55.1% of the variance in intention to join (R² = 0.551). These findings suggest that Generation Z evaluates prospective employers not only based on job security and compensation but also on organizational reputation, workplace flexibility, and supportive work environments. The study contributes to the literature on Generation Z career preferences in the public sector and provides practical implications for BUMN organizations in designing recruitment and talent management strategies